2018
DOI: 10.21873/invivo.11274
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone Inhibits ERK-modulated Tumor Progression in Hepatocellular Carcinoma In Vitro

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Increasing evidences demonstrate that AMF controls cell proliferation, apoptosis, invasion, metastasis, autophagy, transcription and drug-resistance in various types of cancers, such as lung cancer ( Banerjee et al, 2002a ; Banerjee et al, 2002b ; Jung et al, 2017 ; Hu et al, 2018 ; Park and Kim, 2019 ; Shen et al, 2019 ; Kim et al, 2020 ; Chen et al, 2021 ), cervical cancer ( Lee et al, 2011 ), ovarian cancer ( Liu et al, 2017a ; Zhang et al, 2020 ), bladder cancer ( Chiang et al, 2019 ), osteosarcoma ( Pan et al, 2017 ; Lee et al, 2019 ), melanoma ( Guruvayoorappan and Kuttan, 2007 ; 2008b ; a ; Siveen and Kuttan, 2011 ), breast cancer ( Lee et al, 2009 ; Pei et al, 2012 ; Lee et al, 2013 ; Chen et al, 2015 ; Aliyev et al, 2021 ), liver cancer ( Zheng et al, 2016 ; Chen et al, 2017a ; Lee et al, 2018a ; Lee et al, 2018b ; Tsai et al, 2018 ), brain cancer ( Yen et al, 2018 ; Zhaohui et al, 2018 ; Hsu et al, 2019 ; Chen et al, 2020c ), and oral squamous cell carcinoma ( Chen et al, 2020b ) via regulating kinds of signaling pathways ( Figure 2 ). These studies provide a lot of evidences that AMF is a potential effective multi-targeting drug for the prevention and treatment of a variety of cancers.…”
Section: The Multifunctional Biological Activities Of Amentoflavonementioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidences demonstrate that AMF controls cell proliferation, apoptosis, invasion, metastasis, autophagy, transcription and drug-resistance in various types of cancers, such as lung cancer ( Banerjee et al, 2002a ; Banerjee et al, 2002b ; Jung et al, 2017 ; Hu et al, 2018 ; Park and Kim, 2019 ; Shen et al, 2019 ; Kim et al, 2020 ; Chen et al, 2021 ), cervical cancer ( Lee et al, 2011 ), ovarian cancer ( Liu et al, 2017a ; Zhang et al, 2020 ), bladder cancer ( Chiang et al, 2019 ), osteosarcoma ( Pan et al, 2017 ; Lee et al, 2019 ), melanoma ( Guruvayoorappan and Kuttan, 2007 ; 2008b ; a ; Siveen and Kuttan, 2011 ), breast cancer ( Lee et al, 2009 ; Pei et al, 2012 ; Lee et al, 2013 ; Chen et al, 2015 ; Aliyev et al, 2021 ), liver cancer ( Zheng et al, 2016 ; Chen et al, 2017a ; Lee et al, 2018a ; Lee et al, 2018b ; Tsai et al, 2018 ), brain cancer ( Yen et al, 2018 ; Zhaohui et al, 2018 ; Hsu et al, 2019 ; Chen et al, 2020c ), and oral squamous cell carcinoma ( Chen et al, 2020b ) via regulating kinds of signaling pathways ( Figure 2 ). These studies provide a lot of evidences that AMF is a potential effective multi-targeting drug for the prevention and treatment of a variety of cancers.…”
Section: The Multifunctional Biological Activities Of Amentoflavonementioning
confidence: 99%
“…As a heterodimeric transcription factor, NF-κB is composed of p50 and p65 subunits, mediates tumor invasion and metastasis through regulating the expressions of metastasis-associated proteins such as XIAP, MMP-2, MMP-9, cyclinD1, and VEGF ( Rasmi et al, 2020 ). In vitro studies, AMF suppresses cell viability, invasion and migration of different types of cancers, including glioblastoma ( Hsu et al, 2019 ) and HCC ( Lee et al, 2018b ) through inhibiting NF-κB activation and NF-κB-mediated downstream gene expression. Similarly, AMF reduces the invasion ability of NSCLC cells through blocking NF-κB signaling pathway and NF-κB p65 nuclear translocation ( Chen et al, 2021 ).…”
Section: The Multifunctional Biological Activities Of Amentoflavonementioning
confidence: 99%
“…The 10% FBS/RPMI medium were placed into the lower chamber of cell migration/invasion inserts. Cells were allowed for migration or invasion for 48 h, then cells were be fixed with 4% paraformaldehyde in PBS for 30 min at 4˚C, stained with crystal violet solution for 15 min and photographed by microscope (Nikon ECLIPSE Ti-U, Minato City, Tokyo, Japan), and quantified by ImageJ software version 1.50 (National Institutes of Health, Bethesda, MD, USA) (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al found that AME inhibited fatty acid synthesis, increased caspase-3 activity and promoted DNA breakage, thereby accelerating apoptosis of breast cancer cell SKBR3 and inhibiting cell proliferation in a dose-dependent manner to exert antitumor effects [18] . ROB was able to reduce the production of NO, the pro-inflammatory cytokine interleukin-1β (IL-1) and interleukin-6 production in RAW 264.7 macrophages stimulated with lipopolysaccharide (LPS) [19] .…”
Section: Introductionmentioning
confidence: 99%